Pengaruh Kreativitas Boneka Tangan Dari Kaus Kaki Bekas Terhadap Kreativitas Anak di RA Aqila Sintuk Toboh Gadang Kabupaten Padang Pariaman - Pratiwi, Khairunnisa Angriani; Hazizah, Nur (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2023)
Creativity is a person's ability to create and find new things that are meaningful and useful, new ideas, and find ways to solve problems. This will be seen in the work of children who can express ideas and opinions so that they can develop children's creativity. Creativity can be done with innovative activities, one of which is through hand puppets from used socks. Hand puppets are media that are used as media for aids in learning activities that are larger in size than finger puppets and can be put into hands. This type of research is quantitative with experimental methods in the form of quasi-experiments. With a sample of 19 children consisting of Groups B1 and B2. The creative abilities of children after research in the experimental class were more influential than the results of the children's creative abilities in the control class. Overall, there was an increase in the experimental class B1 with a pre-test score of 224 and a post-test of 292, with an average pre-test of 22.4 and a post-test of 29.2. Whereas in the control class B2 there was also an increase in pre-test scores of 161 and post-test of 229, with an average pre-test of 17.8 and post-test of 25.4. Both class scores experienced an increase, but in the experimental class the scores were higher than in the control class. Based on these results it can be seen that there is a significant effect of using Hand Puppets from Used Socks activities on the development of children's creativity at RA Aqila Sintuk Toboh Gadang, Padang Pariaman Regency.